STRATEGI BRANDING DALAM MENINGKATKAN BRAND AWARENESS SEBAGAI PLATFORM EDUKASI MELALUI INSTAGRAM - Putri, Pradifta Irlianda; Refiana Dwi Maghfiroh (Nirta Learning Centre, 2026)
The development of social media, particularly Instagram, has opened opportunities for various educational institutions and learning platforms such to strengthen their image and increase brand awareness among users. This study aims to maximize presence and audience engagement through Instagram. The research employs a qualitative descriptive approach, with data collected through content observation, analysis of Instagram features, and a literature review related to digital branding strategies. The results indicate that features such as Instagram Stories, Reels and Live make significant contributions to enhancing brand awareness. In addition, crafting an authentic brand narrative and fostering community based engagement have proven effective in building emotional connections with the audience. These findings affirm that integrated and adaptive branding strategies aligned with social media characteristics can effectively increase the visibility and image of educational platforms on instagram